Fixed Points of Meromorphic Solutions for Some Difference Equations - Zong-Xuan Chen (Abstract and Applied Analysis, 2013)
We investigate fixed points of meromorphic solutions for the Pielou logistic equation and obtain some estimates of exponents of convergence of fixed points of and its shifts , differences , and divided differences .